Aprendizagem significativa em David Ausubel e Paulo Freire: regularidades e dispersões. - Santana, Marcelo da Fonsêca (2013)
This work aims to investigate regularities and dispersions of the meaningful learning enunciation present in David Ausubel and Paulo Freire s writings. In this process, we employed Michel Foucault s Archeological Analysis of Discourse as the analysis tool. The research corpus is constituted of writings from the referred scholars, which are seen as primary documentary sources. The excavations, carried out in the discursive order about the meaningful learning, made it possible to verify a strong presence of a series of enunciations as its constitutive elements, for example, enunciations about the prior knowledge, mechanical or memoristic learning, learner s passiveness, world view and disposition to learn. Looking into the outcomes from the enunciative series and enunciations analysis, it was possible to observe that such authors defend the importance of prior knowledge as a starting point in the educational process. At the very end, we identified and described the possible contributions that David Ausubel and Paulo Freire have left to every educational context, including the popular education.